Procedures of Translating Dialogue in Carroll’s "Alice’s Adventures in Wonderland" from English into Indonesian - Asriana, Risa Winda; Hartono, Rudi (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
Translation is one activity which needs strategy. In translation there are many strategies which can be used to translate one language to another language. There are technique, method, strategy and procedure. In this study, the researcher provides vivid comprehension on how the translator used the translation procedures to render the meaning of the dialogue. The study attempted to focus on the dialogue translation of Alice’s Adventures in Wonderland by Lewis Carroll and its Indonesian version translated by Agustina Reni Eta Sitepoe. The objectives of the study were to describe the translation procedures used in translating the dialogue in the Alice’s Adventures in Wonderland novel. In conducting this research, the writer used descriptive qualitative approach. This study applied the theory proposed by Vinay and Darbelnet (in Hatim and Munday 2004:30) about translation procedures. The data in this study were words, phrases, clauses and sentences in the form of utterances in the dialog of the novel. The results of the study showed that there were 213 data of dialogues and seven translation procedures found in this study. The seven translation procedures were transposition, literal translation, modulation, adaptation, equivalence, calque, and borrowing. The translation procedures mostly used was transposition (76.99%), followed by literal translation (8.92%), modulation (7.98%), adaptation (2.81%), equivalence (1.87%), calque (1.40%), and borrowing (0.46%). Keywords: Translation Procedures, Dialogues, Alice’s Adventures in Wonderland, English into Indonesia